Pengaruh Kompetensi Auditor Dan Objektivitas Terhadap Kualitas Audit Dengan Audit Fee Sebagai Variabel Moderasi: Studi Kasus pada Kantor Akuntan Publik Wilayah Jakarta - Silvy, Anis; Silfiani, Anis (Jurnal Riset Mahasiswa Akuntansi, 2024)
This research aims to obtain empirical evidence regarding the influence of auditor competency and objectivity on audit quality with audit fees as a moderating variable (case study of KAP auditors in the Jakarta area). This type of research is quantitative research, using associative methods and primary data in the form of questionnaires which are then processed using the SPSS 26 application. The population in this research is all auditors who work at Public Accounting Firms (KAP) in the Tangerang Region, with a total of 105 auditors in respondents. 6 (six) Public Accounting Firms (KAP) located in the West Jakarta and Central Jakarta Regions. The sampling method in this research used the convenience sampling method. The results of this research show that auditor competency does not influence audit quality, objectivity influences audit quality, audit fees do not moderate the relationship between competency and audit quality, audit fees do not moderate the relationship between objectivity and audit quality.